The Effectof Company Culture, Religiosity, and Commitment on Performance Through Employee Satisfactionas Intervening Variableof Sharia Banking in Pekanbaru - Alan Asyari Alfalah; Yuswar Z Basri; Tatik Marianti; Zulhelmy M Hatta (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2020)
ABSTRACT This study aims to analyze the Effect of Company Culture, Religiosity, and Commitment on Performance through Employee Satisfaction as Intervening Variable of Sharia Banking in Pekanbaru. It utilized primary data that was collected using a questionnaire with a total of 250 respondents. Respondents in this study were employees of Sharia Commercial Banks in Riau Province. This study found the following interesting findings: company culture has a positive and significant effect on job satisfaction and on the performance of sharia bank employees,religiosity has a positive and significant effect on employee performance; organizational commitment has an effect on job satisfaction and on employee performance; job satisfaction has an effect on employee performance and job satisfaction can mediate organizational culture of the company on employee performance in Pekanbaru where researchers want to see the indirect effect on performance; job satisfaction can mediate religiosity on employee performance in Pekanbaru where researchers want to see the indirect effect on employee performance; and job satisfaction can mediate organizational commitment on employee performance in Pekanbaru where researchers want to see indirect effect on employee performance